Răspuns:
E(x)=2[tex](x+3)^{2}[/tex]-(2+x)(x-2)-2(5x+7)
Explicație pas cu pas:
2[tex](x-3)^{2}[/tex]-(2+x)(x-2)-2(5x+7)≥7
2[tex](x-3)^{2}[/tex] = 2([tex]x^{2}[/tex]+6x+9) = 2[tex]x^{2}[/tex] + 12x + 18
-(2+x)(x-2) = -(4+[tex]x^{2}[/tex]) = 4 - [tex]x^{2}[/tex]
-2(5x+7) = -10x - 14
E(x) = 2[tex]x^{2}[/tex] + 12x + 18 + 4 - [tex]x^{2}[/tex] -10x - 14 = [tex]x^{2}[/tex] + 2x +8
E(x)≥7
[tex]x^{2}[/tex] + 2x +8 ≥ 7 ⇒ [tex]x^{2}[/tex] + 2x +1 ≥ 0
Δ = [tex]b^{2}[/tex] - 4*a*c = 4-4 = 0
[tex]x_{1}=[/tex] [tex]x_{2}=[/tex] -b/2a = -2/2 = -1